2016
DOI: 10.1152/advan.00002.2015
|View full text |Cite
|
Sign up to set email alerts
|

An active, collaborative approach to learning skills in flow cytometry

Abstract: Advances in science education research have the potential to improve the way students learn to perform scientific interpretations and understand science concepts. We developed active, collaborative activities to teach skills in manipulating flow cytometry data using FlowJo software. Undergraduate students were given compensated clinical flow cytometry listmode output (FCS) files and asked to design a gating strategy to diagnose patients with different hematological malignancies on the basis of their immunophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In this study, after sorting the Treg cells in the mouse intestine and spleen, the purity of the Treg cells both in spleen and intestine reached about 80% (Additional file 2), suggesting that the purity of CD4 + CD25 + Foxp3 + Treg cells can meet the requirements ( Jenkins et al, 2015 ; Fuller et al, 2016 ).…”
Section: Resultsmentioning
confidence: 70%
“…In this study, after sorting the Treg cells in the mouse intestine and spleen, the purity of the Treg cells both in spleen and intestine reached about 80% (Additional file 2), suggesting that the purity of CD4 + CD25 + Foxp3 + Treg cells can meet the requirements ( Jenkins et al, 2015 ; Fuller et al, 2016 ).…”
Section: Resultsmentioning
confidence: 70%
“…The second course consisted of a three‐hour tutorial for undergraduate pathology students which focused on establishing a more basic understanding of flow cytometry through active learning. By utilizing real flow cytometry data in a computer learning center, the researchers were able to see student engagement and improved skills in both their 3‐day and 3‐hour courses . Ott et al report about a course with an in‐depth study of immunological tools, including half of a semester focused on flow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…There are important lessons from evidence‐based research in flow cytometry, especially in the development of applicable instruction and student participation yielding better learning. Fuller et al reported the success of two short flow cytometry courses targeted to different audiences . The first reported on students which had direct applications for flow cytometry in their research, so the 3‐day course focused mainly on technical skills and data interpretation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations